2008
DOI: 10.1111/j.1468-2982.2008.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cerebral Vasomotor Reactivity in Migraine With Aura: An Autoregulation Disorder? A Transcranial Doppler and Near-Infrared Spectroscopy Study

Abstract: Migraine with aura (MA) is associated with changes in cerebral blood flow (CBF), whereas the role of cerebral autoregulation is uncertain. This study aimed to evaluate basal CBF, cerebral blood volume (CBV) and vasomotor reactivity (VMR) in MA patients. Twenty-one controls and 16 MA patients (eight with side predominance) underwent simultaneous examination of flow velocity in the middle cerebral arteries by transcranial Doppler (TCD) and of near-infrared spectroscopy (NIRS) parameters [oxygen haemoglobin satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 36 publications
4
55
0
Order By: Relevance
“…Nedeltchev et al reported that migraine patients suffer from an autoregulation disorder, based on flow response behaviour in both MCAs and (31). Dora and Balkan studied patients with migraine and a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nedeltchev et al reported that migraine patients suffer from an autoregulation disorder, based on flow response behaviour in both MCAs and (31). Dora and Balkan studied patients with migraine and a control group.…”
Section: Discussionmentioning
confidence: 99%
“…TCD can be used to evaluate the flow characteristics of intracranial arteries, microemboli, and vasomotor reactivity (VMR). The acoustic window is the cranial bone's thinnest region for using TCD and the transtemporal window facilitates insonation of the ipsilateral middle cerebral artery (MCA), anterior cerebral artery (ACA), and posterior cerebral artery (PCA) (13,15,30,31). Neuronal activity is correlated with changes in local cerebral blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…107 Further, when using other vasoactive stimuli, such as hypercapnia, the NIRSderived percent hyperemic response is markedly less (1À15% increases vs. 20À100% increases) of that demonstrated by NIRS. 108 This discrepancy, likely reflecting different physiological mechanisms, potentially impacts the sensitivity of NIRS to detect significant differences between clinical and control populations. 109 Clearly, more studies are needed to address the congruency of TCD and NIRS signals during NVC.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…Results are not consistent in literature, since the testing procedures may vary from group to group. In previous studies, we documented a limited vasodilation capability in migraine sufferers [12], but Vernieri et al recently found an increase in the vascular response of migraineurs [20], possibly mediated by a dysfunction in the autonomic control. Such experiments, conducted on groups of patients, document the limited reliability of time-derived parameters when used to assess autoregulation.…”
Section: Introductionmentioning
confidence: 63%
“…It has been proven that aura determines an alteration in the subjects' cerebral hemodynamics. Even if cerebral autoregulation impairment has been observed during MwA attacks, it is still unclear whether MwA sufferers present a normal autoregulation during attack-free periods [20]. The aim of our study was twofold: (i) first, to accurately measure the VLF and LF power changes in the NIRS signals of migraineurs during active stimulations; and (ii) second, to document possible differences in the cerebral hemodynamics of MwA and MwoA sufferers.…”
Section: Introductionmentioning
confidence: 99%